2018
DOI: 10.13157/arla.65.1.2018.ra1
|View full text |Cite
|
Sign up to set email alerts
|

Species-Area Relationships of Specialist Versus Opportunistic Pampas Grassland Birds Depend on the Surrounding Landscape Matrix

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…The surrounding landscape matrix influences the responses of species in habitat fragments (Pretelli et al, 2018), and responses to landscape attributes provide information about improvements in habitat management (Kroll et al, 2014). Increasing the amount of native vegetation may provide additional habitat and can be considered a key driver of species richness (Lindenmayer et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The surrounding landscape matrix influences the responses of species in habitat fragments (Pretelli et al, 2018), and responses to landscape attributes provide information about improvements in habitat management (Kroll et al, 2014). Increasing the amount of native vegetation may provide additional habitat and can be considered a key driver of species richness (Lindenmayer et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found a significant positive relationship between bird species diversity and the amount of native vegetation in the landscape surrounding the patch of habitat where they occur (e.g., Haire et al, 2000;Lindenmayer et al, 2010;Wentworth et al, 2010). Landscapes with large areas of continuous grasslands significantly enhance the richness and abundance of grassland-specialist birds (Codesido et al, 2013;Pretelli et al, 2018). Therefore, the surrounding context has been considered a more important issue than assessing the patch size and degree of isolation (Collinge et al, 2003;Lindenmayer et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Historic ones are presumed to often derive from ancient migratory routes of wildlife (Manzano Baena & Casas, 2010) Drove roads have been observed to have a strong effect in increasing multifunctionality of the landscape by working as linear grasslands and increasing heterogeneity at the large scale, translating into an increase of biodiversity in diverse taxonomic groups such as plants (Azcárate et al, 2013a), ants (Azcárate et al, 2013b; Hevia et al, 2013) or even bees, linked with important pollination services (Hevia et al, 2016). Given the proven capacity of livestock in achieving long-distance dispersal along drove roads, both by endozoochory (Manzano, Malo & Peco, 2005) and by epizoochory (Manzano & Malo, 2006), mobile pastoralism taking place in drove roads could potentially mitigate the consequences of population isolation, which is a major outcome of fragmentation processes (Fahrig, 2003; Mitchell et al, 2015), especially in a grassland context (Pretelli, Isacch & Cardoni, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Historic ones are presumed to often derive from ancient migratory routes of wildlife (Manzano Baena & Casas 2010) Drove roads have been observed to have a strong effect in increasing multifunctionality of the landscape by working as linear grasslands and increasing heterogeneity at the large scale, translating into an increase of biodiversity in diverse taxonomic groups such as plants (Azcárate et al 2013a), ants (Azcárate et al 2013b;Hevia et al 2013) or even bees, linked with important pollination services (Hevia et al 2016). Given the proven capacity of livestock in achieving long-distance dispersal along drove roads, both by endozoochory (Manzano et al 2005) and by epizoochory (Manzano & Malo 2006), mobile pastoralism taking place in drove roads could potentially mitigate the consequences of population isolation, which is a major outcome of fragmentation processes (Fahrig 2003;Mitchell et al 2015), especially in a grassland context (Pretelli et al 2018).…”
Section: Introductionmentioning
confidence: 99%